Green Tourism Implementation Strategy in Ecotourism Development in Garut Regency - Adiatma, Dani; Rukma, Deden Firman Syuyaman (International Journal of Green Tourism Research and Applications, 2025)
Garut Regency holds considerable potential for ecotourism development, yet faces a persistent implementation gap characterized by poor infrastructure, environmental degradation, and weak policy enforcement, despite supportive regulations. This study aims to comprehensively analyze the internal and external factors influencing Garut's ecotourism and formulate integrated green tourism strategies to address this gap. Employing a qualitative descriptive case study approach, data were obtained through literature review and policy document analysis, including scholarly articles, local policy documents (e.g., RIPPDA, strategic plans), and other credible secondary sources. The data were analyzed using qualitative content analysis within a SWOT framework. The findings indicate that while Garut benefits from diverse natural and cultural resources and a rising interest in green tourism, infrastructural deficiencies, substandard services, environmental threats, and lax law enforcement offset these strengths. To overcome these barriers, four strategic directions are proposed: (1) strengthening governance and policy enforcement, (2) promoting community-based ecotourism, (3) developing green infrastructure and service quality standards, and (4) executing authentic green marketing initiatives. This study underscores the urgency of closing the implementation gap. It offers actionable recommendations for stakeholders including government, communities, and the private sector to promote authentic and sustainable ecotourism practices at the local level.